2020
DOI: 10.1038/s41598-020-59393-6
|View full text |Cite
|
Sign up to set email alerts
|

Reduced Resting-State Connectivity in the Precuneus is correlated with Apathy in Patients with Schizophrenia

Abstract: A diagnosis of schizophrenia is associated with a heterogeneous psychopathology including positive and negative symptoms. The disconnection hypothesis, an early pathophysiological framework conceptualizes the diversity of symptoms as a result of disconnections in neural networks. in line with this hypothesis, previous neuroimaging studies of patients with schizophrenia reported alterations within the default mode network (DMN), the most prominent network at rest. The aim of the present study was to investigate… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(20 citation statements)
references
References 52 publications
3
15
0
Order By: Relevance
“…That is, primates have evolved cognitive mechanisms to understand and analyze complex social interactions ( Freiwald, 2020 ). Among the multiple cellular components with an intrinsic connectivity and functional networks in the human cerebral cortex (see further discussion in van den Heuvel et al, 2015 ), some large-scale circuits have been studied for their roles in resting state, attention and task-related activity or cognitive functions ( Ng et al, 2016 ; Deming and Koenigs, 2020 ; Forlim et al, 2020 ; Kolb and Whishaw, 2021 ). High signal coherence within these networks makes the sub-components functionally coupled along varied timeframes ( Ng et al, 2016 and references therein), such as in the DMN, which comprises the PC ( Cavanna and Trimble, 2006 ) and the posterior cingulate cortex, the medial prefrontal cortex, and the bilateral intraparietal cortex/angular gyrus; in the “salience network” (SN), including the bilateral anterior insula and the dorsal ACC; and, in the “executive control network” (ECN) including the “frontoparietal network” (FPN) composed of bilateral middle frontal gyri and supramarginal gyri/inferior parietal lobe ( Hidalgo-Lopez et al, 2021 and references therein), the intraparietal sulcus, and dorsal prefrontal cortex ( Ptak, 2012 ; Deming and Koenigs, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…That is, primates have evolved cognitive mechanisms to understand and analyze complex social interactions ( Freiwald, 2020 ). Among the multiple cellular components with an intrinsic connectivity and functional networks in the human cerebral cortex (see further discussion in van den Heuvel et al, 2015 ), some large-scale circuits have been studied for their roles in resting state, attention and task-related activity or cognitive functions ( Ng et al, 2016 ; Deming and Koenigs, 2020 ; Forlim et al, 2020 ; Kolb and Whishaw, 2021 ). High signal coherence within these networks makes the sub-components functionally coupled along varied timeframes ( Ng et al, 2016 and references therein), such as in the DMN, which comprises the PC ( Cavanna and Trimble, 2006 ) and the posterior cingulate cortex, the medial prefrontal cortex, and the bilateral intraparietal cortex/angular gyrus; in the “salience network” (SN), including the bilateral anterior insula and the dorsal ACC; and, in the “executive control network” (ECN) including the “frontoparietal network” (FPN) composed of bilateral middle frontal gyri and supramarginal gyri/inferior parietal lobe ( Hidalgo-Lopez et al, 2021 and references therein), the intraparietal sulcus, and dorsal prefrontal cortex ( Ptak, 2012 ; Deming and Koenigs, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…The protein encoded by the gene DISC1 (disrupted in schizophrenia) had an evolutionary change in the line leading to humans, is related to neuronal migration and dendritic branching, and is preferentially expressed by VENs ( Allman et al, 2010 ; Cauda et al, 2014 ; see the GWAS atlas at https://atlas.ctglab.nl for current data on current DISC1 associations). In addition, reduced resting-state connectivity in the PC was correlated with apathy in patients with schizophrenia ( Forlim et al, 2020 ). Apathy is a motivational disorder incurring reduced or loss of goal-directed behavior, goal-directed cognitive processes, and emotion ( Forlim et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Connectivity intensity in this area is negatively correlated with the severity of negative symptoms, more speci cally with the apathy domain (Forlim et al, 2020). Gangadin et al (2021) also demonstrated a reduction in the connectivity of the hypocampal-mesencephal-striate network in patients with schizophrenia.…”
Section: Introductionmentioning
confidence: 94%
“…The DMN has also been identified as relevant for a number of clinical variables including symptom severity, 20 long-term clinical outcomes, 21 and response to antipsychotic treatment. 22 , 23 Importantly, baseline functional connectivity of the DMN was found to be the single most positive predictor for subsequent response to antipsychotic treatment in an assessment of five key functional brain networks in early illness schizophrenia patients.…”
Section: Introductionmentioning
confidence: 99%